Transferência de elétrons em complexos de Rutênio (II) Perileno Diimida - Tiyoda, Anderson Jun (Universidade Federal de São Carlos, 2024)
Ruthenium(II) polypyridyl complexes are among the most studied metal complexes, with numerous articles and book chapters dedicated to them due to their properties being used in technological and medical fields, such as applications in photocatalysis and dynamic phototherapy, among others. Photochemistry is one of the most important processes for living beings due to photosynthesis, which starts from simple molecules and sunlight to efficiently produce a complex carbohydrate and oxygen gas, the last being essential for aerobic living beings. Ru(II) complexes with perylene diimide (PDI) ligands exhibit interesting characteristics for studies of electron and charge transfer, such as long triplet state lifetimes in the nanosecond range. Due to this long lifetime, the complexes can be applied in the production of singlet oxygen and for photodynamic therapy.
Electron transfer in Rutenium(II) perylenediimide complexes
Keywords: Complexos polipiridínicos de rutênio(II); Transferência de elétrons; Perileno diimidas; Ruthenium(II) polypyridyl complexes; Electron-transfer; Perylene diimide; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FOTO-QUIMICA INORGANICA